2016
DOI: 10.1016/j.jvs.2015.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Low wall shear stress predominates at sites of abdominal aortic aneurysm rupture

Abstract: This computational study was the first to assess blood flow characteristics at the site of infrarenal AAA rupture in realistic aortic geometries. In contradiction to our initial hypothesis, rupture occurred not at sites of high pressure and WSS but rather at regions of predicted flow recirculation, where low WSS and thrombus deposition predominated. These findings raise the possibility that this flow pattern may lead to thrombus deposition, which may elaborate adventitial degeneration and eventual AAA rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(133 citation statements)
references
References 33 publications
7
121
1
4
Order By: Relevance
“…37 Several retrospective studies indicate that finite element analysis can identify areas with increased risk of aneurysm expansion and rupture. [38][39][40] A study of 30 asymptomatic, 15 symptomatic, and 15 ruptured AAA suggested that PWRI was the parameter that best distinguished between asymptomatic and symptomatic AAAs. 40 The same group reported that regions of the AAA with increased PWRI had increased histopathological degeneration on examination of aortic wall specimens obtained at surgical repair.…”
Section: Biomechanical Imagingmentioning
confidence: 99%
“…37 Several retrospective studies indicate that finite element analysis can identify areas with increased risk of aneurysm expansion and rupture. [38][39][40] A study of 30 asymptomatic, 15 symptomatic, and 15 ruptured AAA suggested that PWRI was the parameter that best distinguished between asymptomatic and symptomatic AAAs. 40 The same group reported that regions of the AAA with increased PWRI had increased histopathological degeneration on examination of aortic wall specimens obtained at surgical repair.…”
Section: Biomechanical Imagingmentioning
confidence: 99%
“…With this in mind, we approximated the blood flow as laminar and considered the blood to be an incompressible fluid with a density of 1050 kg/m 3 . The walls of the arteries were characterised by no-slip, rigid wall boundary conditions [5,6,32,35,54,55] and the viscosity was modelled using a non-Newtonian approximation (Carreau-Yasuda, as implemented by Biasetti et al [44]; [56]). By using a non-Newtonian model, as opposed Newtonian, we can capture the macro-scale shear-thinning of the blood, allowing a one-way Lagrangian particle transport model to provide a good prediction of individual blood-cell trajectories within the continuous phase (blood).…”
Section: Physical Assumptions and Boundary Conditionsmentioning
confidence: 99%
“…Furthermore, Rayz et al [31] observed thrombus deposition in certain regions of patient-specific intracranial geometries with an increase in residence time and low WSS. More recently, Boyd et al found that AAA rupture tended to occur in thrombus afflicted regions with predicted flow recirculation and low WSS [32]. In addition, it has been shown that regions of low, oscillatory WSS provide a well-described mechanical stimulus that promotes the inflammatory process by inducing an oxidative response in endothelial vascular cells [33].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, image acquisition, quantification, and analysis methods need standardization to ensure rigor, reproducibility, validity, and reliability. Another potential problem is that NP localization is unlikely to reflect the hemodynamic forces on the aortic wall, which are also relevant to AAA rupture risk (72). …”
Section: Studies Assessing Nps In Aaa Imagingmentioning
confidence: 99%